The Contribution of Root Turnover on Biological Nitrification Inhibition and Its Impact on the Ammonia-Oxidizing Archaea under Brachiaria Cultivations - Satoshi Nakamura; Papa Sarr Saliou; Minako Takahashi; Yasuo Ando; Guntur Venkata Subbarao (Agronomy, 2020)
Aims: Biological nitrification inhibition (BNI) has been reported as an emerging technology to control soil nitrifier activity for effective N-utilization in cropping systems. Brachiaria have been reported to suppress nitrifier populations by releasing nitrification inhibitors from roots through exudation. Substantial BNI activity has been reported to be present in the root tissues of Brachiaria grasses; however, BNI contribution, such as root turnover, has not been addressed in previous studies. The present study aimed to clarify the contribution of root turnover on BNI under Brachiaria cultivations and its impact on nitrifier populations. Methods: We monitored root growth, changes in ammonia-oxidizing bacteria (AOB) and ammonia-oxidizing archaea (AOA) numbers, nitrification rate, and available nitrogen (N) content under seven germplasm lines of Brachiaria, for 18 months with seasonal profile sampling. Results: Brachiaria cultivation increased soil NH4+-N, available N, and total soil carbon levels. Though we did not find any correlation between the changes in AOB populations and potential nitrification, the potential nitrification rate decreased when AOA populations decreased. Multiple regression analysis indicated that BNI substances from root tissue turnover had a significant contribution to the BNI function in the field. Conclusion Results indicated that the inhibitory effect of BNI was mostly evident in AOA, and not in AOB, in this study. Brachiaria cvs. ‘Marandu’, ‘Mulato’, and ‘Tupy’ had the most substantial BNI effect among the seven cultivars evaluated. The estimated total BNI activities and available N content of root tissue explained the observed nitrification inhibition. In conclusion, the release of BNI substances through plant decomposition contributes to the decrease in the abundance of AOA, and thus the inhibition of nitrification under Brachiaria cultivation.